Urogenital management in cloaca: An alternative approach - Harshjeet Singh Bal; Sudipta Sen; Cenita Sam; Jacob Chacko; John Mathai; S R Regunandan (Wolters Kluwer Medknow Publications, 2017)
Introduction: In the management of cloaca, there is concern that dissection of the urogenital sinus in early childhood with the aim of total anatomical correction is hazardous. Avoiding such mobilization and providing mitrofanoff channel, when needed, till peripubertal period reduces complications and is technically easier. Materials and Methods: Forty-three cases of cloaca were managed in the period 2004-2016. Case records and radiology were reviewed retrospectively. The follow-up evaluation was done by looking into voiding history, bowel movements, and menstruation history. Results: There were three groups of children, namely, those with no reconstruction done elsewhere except a diverting fecal stoma (Group I, n = 25), those who had undergone anorectal correction elsewhere with no attempt at urogenital reconstruction (Group IIA, n = 13), and tho with attempted bowel and genitourinary reconstruction elsewhere (Group IIB, n = 5). The Group I children (one still awaiting reconstruction) underwent early rectal reconstruction followed by expectant management of the urogenital apparatus. The 18 referred cases had multiple problems, chiefly urogenital, of congenital or iatrogenic origin. While urinary reconstruction included bladder augmentation, ileal neobladder, bladder neck closure, and ureteric reimplantation, the foundation of urinary management was intermittent catheterization through mitrofanoff stoma and the avoidance of any dissection of the cloacal common channel. Surgery on the genital tracts included drainage of hydrocolpos, perineal surgery for low vaginae and abdominoperineal vaginoplasty for high vaginae in the peripubertal period with or without bowel supplementation. Spontaneous voiding was maintained in 17 of 25 (68%) Group I girls (including one death later from intestinal complications), 7 of 13 (54%), Group IIA girls, and 1 of 5 (20%) Group IIB girls. Painless menstruation was noted in eight postpubertal girls, three through the cloacal channel (awaiting reconstruction) and five through the reconstructed vagina. Most of the children are on a bowel management program for fecal cleanliness with washouts through the neoanus or Malone's stoma. Conclusion: We report a nonconventional approach to cloaca based on avoiding dissection of or around the common channel for urethrovaginal reconstruction, opting for mitrofanoff stoma for intermittent catheterization, when needed, and late vaginal reconstruction. We believe this approach has reduced the overall need for intermittent catheterization.